SOCIAL INNOVATION IN THE CULTURAL SECTOR: THE CASE OF PJE/PRODIGIUM - Saldanha, Fabio Prado; Delgado, Natalia Aguilar; Pozzebon, Marlei (Revista Brasileira de Casos de Ensino em Administração, 2021)
This case examines the major challenges faced by Productions Jeun’Est (PJE) and Prodigium, a social enterprise working in the cultural sector. The profits generated by Prodigium’s activities in the entertainment field are invested in the PJE training program that aims to increase the social inclusion of vulnerable youth by training them to be technicians in the cultural market. By studying this case, students are expected to understand the elements of a social business model, to analyze the role of the different elements forming a social innovation and to evaluate the challenges of planning its transfer to another context.

‘Tecnologia social’ and social change: the case of Agência de Redes in Rio de Janeiro - Saldanha, Fabio Prado; Aguilar-Delgado, Natalia; Pozzebon, Marlei (Revista Brasileira de Casos de Ensino em Administração, 2019)
The case provides an opportunity to understand how tecnologia social – a South American concept that might be seen as an equivalent to social innovation – can help promote social change. To illustrate the potential of social technologies, the case of Agência de Redes is presented. The case is intended for use at both the undergraduate and graduate levels. Its purpose is to promote the discussion of the South American concept of tecnologia social, as well as to analyse of one particular tecnologia social using a conceptual model to understand the mechanisms that might promote social change.